The profile of the research teacher: towards its dimensions and its strengthening - Vásquez Villanueva, Salomón (2020)
The study has been carried out with the double objective: to determine the dimensions of the profile of the research teacher and to select the procedures to strengthen the referred profile. The profile of the research professor has become a vast and complex universe, controversial, even adverse in several aspects, in which universe many questions are posed, leaving no objective, clear, precise, and convincing answers. In this context, the profile of the research teacher has been studied: its dimensions and procedures to strengthen them. It is concluded that the profile of the research teacher presents the following dimensions: pedagogical, professional academic, emotional intelligence, ethics, publication, permanence and visibility. In addition, it is strengthened through the guidance of the expert investigator, state legislation, investigative training, and attendance at research events.